(untitled) (Sociologisk Forskning, 2017)
Population ageing and international migration are two of the most significant challenges that Sweden is facing today. These – combined with the scholarly debate on the ethics-of-care that notions such as ‘caring democracies’ have re-ignited – raise questions about how media representations of elderly care and migration are shaped. This research note gives insight into how care, and migrant care workers, are regarded in one of the world’s most egalitarian societies. In doing so, it suggests that the intersection between population ageing and international migration is an abundant source of information about societies’ moral compasses.